2001
DOI: 10.1002/app.1326
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly(DL‐lactide‐co‐glycolide) nanoparticles without surfactant

Abstract: The preparation of poly(DL-lactide-co-glycolide) (PLGA) nanoparticles was performed by a dialysis method without surfactant or emulsifiers. The size of the PLGA nanoparticles prepared from dimethylacetamide (DMAc) as an initial solvent was smaller than that from acetone. The sizes of the PLGA nanoparticles from DMAc and acetone were 200.4 Ϯ 133.0 and 642.3 Ϯ 131.1 nm, respectively. The effects of the initial solvent selected to dissolve the copolymer and the lactide:glycolide ratio were investigated. The PLGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Although the mechanism is not fully understood at present, it is thought that the principle of PLGA nanoparticles formation by the dialysis procedure may be based on a mechanism similar to the Fessi et al method, that is, by subsequent hydrophobic interactions among the polymer chains [6]. …”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism is not fully understood at present, it is thought that the principle of PLGA nanoparticles formation by the dialysis procedure may be based on a mechanism similar to the Fessi et al method, that is, by subsequent hydrophobic interactions among the polymer chains [6]. …”
Section: Resultsmentioning
confidence: 99%
“…Since degradation is triggered by water that hydrolyzes the functional groups 30. Polydispersity index ( M w/ M n) is nearly unchanged, indicating that random chain cleavage is the likely degradation mechanism 40. On the other hand, the NPs with BCDen group degrade faster than those with CDen group.…”
Section: Resultsmentioning
confidence: 99%
“…Polyvinyl alcohol (PVA) is an uncharged and relatively hydrophilic polymer [9, 10] that has been widely used as a carrier polymer in drug delivery devices, such as sustained-release particles and hydrogels [11, 12], or as a surfactant for formulating polymeric drug carriers, such as the Lupron Depot ® [13, 14]. We observed that using PVA as a surfactant during particle formulation by the nanoprecipitation or emulsion methods leads to the formation of mucoadhesive nanoparticles [1517].…”
Section: Introductionmentioning
confidence: 99%